EKSISTENSI TARI MONDOTAMBE PADA MASYARAKAT TOLAKI DI KECAMATAN UNAAHA KABUPATEN KONAWE ABAD XVIII-XX - Erlanda Ian Pratiwi Mardin; Hayari, Sarman (Journal Idea of History, 2019)
This study aims to describe the existence of Mondotembe dance in the Tolaki community in Unaaha District, Konawe Regency. The method used in this study was the historical method developed by Kuntowijoyo with the following stages: (1) Selection of topics, (2) Collection of sources, (3) Verification, (4) Interpretation, and (5) Historiography. Literature study used consists of historical concepts and theories, cultural concepts and theories, dance concepts, cultural change concepts, concepts of symbolic meaning, and historiographic review. The results showed that: (1) Mondotambe dance was born during the reign of the Konawe Kingdom centered in Unaaha in the XVIII century. The Mondotambe dance was a dance which dedicated to welcoming the Tamalaki (warriors) who have just returned from the battlefield against the Tobelo pirates with victory. (2) In addition to welcoming the returning soldiers from the battlefield, Mondotambe dance functionS were as a welcoming dance for guests of the Konawe Kingdom in Unaaha, the inauguration of a building, the opening of an activity organized by Konawe Regency government agencies and events. rituals like marriage. The Mondotambe dance was performed by teenage girls and two young men as a companion (3) Changes to the Mondotambe dance appear in: a). Implementation aspects in terms of time and place, b). Accompaniment, c). Clothing and accessories for dancers and musicians, d). Musical accompaniment instrument. (4) The symbolic meaning contained in every detail of the movements and sounds that accompany the Mondotambe Dance, including: a). Hand gesture means the symbol of acceptance and reception, b). Female dancers become a symbol of tenderness and beauty, and c). The sound of "Gong" sounds as an invitation to the public to welcome one or a group of honored guests. Keyword: Existence, Mondotambe Dance, Function, Symbolic Meaning